2023
DOI: 10.1021/acs.energyfuels.2c03723
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Microstructure and Petrophysical Properties of Undeformed and Naturally Deformed Shales

Abstract: Structural deformation is one of the main impacts responsible for understanding the hydrocarbon accumulation mechanism. Predicting its function in gas storage and migration in a microscopic scale is thus a significant issue in predicting reservoir quality. The purpose of this article is to make a comparative study on the microstructure and petrophysical properties of undeformed and naturally deformed shales developed in the Southeast Sichuan Basin. The results show that (1) organic pores, ranging from 10 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…SEM images showing the types of OM pores. Figure A was adapted with permission from ref . Copyright 2023 American Chemical Society.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…SEM images showing the types of OM pores. Figure A was adapted with permission from ref . Copyright 2023 American Chemical Society.…”
Section: Resultsmentioning
confidence: 99%
“…Low-pressure gas adsorption and mercury intrusion porosimetry are commonly used to measure the pore size distribution for multipore structure materials. ,,,, Numerous studies have shown that the pore system in shale is dominated by nanopores (pore size <1000 nm) and a small number of fracture pores. On the basis of the classification of the International Union of Pure and Applied Chemistry (IUPAC), pores are split into micropores (pore size <2 nm), mesopores (pore size between 2 and 50 nm), and macropores (pore size >50 nm). A plot of incremental pore volume versus pore diameter for low-pressure gas adsorption and mercury intrusion porosimetry is commonly used to illustrate the pore size distribution …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations